Gender Resource Accessibility and Profitability among Groundnut Producers in Hong Local Government Area of Adamawa State, Nigeria - C. O, Ojo; A. A, Ghide; E, Phanuel (Asian Journal of Agriculture and Rural Development, 2013)
The study aimed to examine gender resource accessibility and profitability among groundnut producers in Hong Local Government Area of Adamawa State, Nigeria. Multistage sampling technique was used to sample 54 respondents (27 male and 27 female) by the use of a structured questionnaire. The data from the survey were analysed using frequency distribution and gross margin analysis. The results showed that the men were generally older and more experienced than the women with 77.8% and 55.5% of men and women respectively being over 40 years of age and 51.9% and 37.1% of men and women respectively having farming experience of over 20 years. The perception of the respondents was that men had more access to resources and opportunities that enhance productivity (land, labour, chemicals, market and education) than women (fertilizer, seeds, and cooperatives). Gross margin per hectare of men was N62, 693 while that of women was N37, 732. It was recommended that credit provision in cash and kind to women by Government and other relevant organisations be encouraged in order to give women improved access to production resources to increase women’s productivity and profitability.